2014
DOI: 10.1007/s10120-014-0362-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of venous invasion in stage IB node-negative gastric cancer

Abstract: Background Little is known about risk factors for recurrence in stage IB gastric cancer without lymph node metastasis. The aims of this study were to determine prognostic factors associated with long-term survival and to clarify patterns of recurrence. Methods We retrospectively reviewed the medical records of 130 patients with primary gastric cancer who underwent gastrectomy at Kitasato University East Hospital from 2001 through 2010 and analyzed clinicopathological characteristics associated with survival an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Because both v2 or v3 and LNR of > 0.16 cannot be diagnosed preoperatively, postoperative adjuvant chemotherapy would likely improve prognoses of such high-risk patients. Either v2 or v3 is reportedly an independent prognostic factor for Stage IB node-negative gastric cancer[25]. Venous invasion theoretically predicts hematological metastases, and lymphatic invasion, LN metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Because both v2 or v3 and LNR of > 0.16 cannot be diagnosed preoperatively, postoperative adjuvant chemotherapy would likely improve prognoses of such high-risk patients. Either v2 or v3 is reportedly an independent prognostic factor for Stage IB node-negative gastric cancer[25]. Venous invasion theoretically predicts hematological metastases, and lymphatic invasion, LN metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have identified a number of prognostic factors for gastric cancer, with lymph node metastasis being the strongest prognostic factor after curative resection (5), and venous invasion only reported as an unfavourable prognostic factor in patients with IB stage gastric cancer without lymph node metastasis (12). ECJ carcinoma patients with venous invasion may thus have a poor prognosis compared with gastric cancer, and may benefit from the effective use of adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Submucosal invasion was subdivided into SM1 (tumor invasion less than 500 μm from the muscularis mucosa) or SM2 (tumor invasion more than 500 μm from the muscularis mucosa). The subdivision of venous invasion (v0, v1, v2, and v3) was also conducted using a similar manner [25]. Venous invasion was determined by Elastica van Gieson staining.…”
Section: Evaluation Of Pathologic Specimens After Endoscopic Lesion Rmentioning
confidence: 99%